PENGARUH METODE PEMBELAJARAN PAIKEM TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS III SDN 5 TULUNG SELAPAN - Mujadilah; Ramanata Disurya; Hermansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem in this study is the low student learning outcomes in Indonesian subjects caused by the lack of use of learning methods, the learning methods used are still conventional so that students are less active and less interested in the learning taught by teachers, especially in Indonesian lessons, so learning methods and approaches are needed that create active, innovative, creative, effective and fun learning (PAIKEM) so that students are enthusiastic about participating in the teaching and learning process to improve student learning outcomes. This study aims to determine whether there is an effect of using the PAIKEM method on Indonesian language learning outcomes class III students of SDN 5 Tulung Selapan. The research method is True Experiment Designs (pure experiments) using a pretest-posttest control group design, with a sample population of 2 classes. Class III A as the experimental class and class III B as the control class. The data collection technique used is a test to measure student learning outcomes and documents. The data analysis technique used is the normality test and hypothesis testing. Based on the results of the research analysis, it was found that there was an effect of using the PAIKEM method on the learning outcomes of Indonesian language students in grade III SD Negeri 5 Tulung Selapan, with an average pretest value of 38.25 with a standard deviation of 9.216 and a posttest of 75.00 and a standard deviation of 9.032 with Sig. (2- N tailed) 0.000. This result is evident from the value of -tcount > -ttable, namely -14,735 <0.456. So thus Ho is rejected and Ha is accepted.